Facilitators and barriers to building research capacity among clinical nurses: A systematic review protocol - Jinglin Song; Yunhong Lei; Luhuan Yang; Jordan Tovera Salvador; Daying Long (PLoS ONE, 2025)
Background Clinical nurses’ research capacity is essential for building a research-active nursing workforce and advancing evidence-based practice. Despite increasing global attention, few systematic reviews have examined the current state of nurses’ research capacity or the factors influencing its development. Objective This protocol outlines a systematic review designed to evaluate clinical nurses’ research capacity and to identify the key barriers and facilitators to its improvement across diverse healthcare contexts. Methods The review will follow PRISMA guidelines. Eight databases—PubMed, Cochrane Library, Embase, CINAHL, Web of Science, Scopus, CNKI, and Wanfang—will be searched for relevant quantitative, qualitative, and mixed-methods studies. Study selection, data extraction, and quality appraisal will be performed independently by two reviewers using the Mixed Methods Appraisal Tool (MMAT). Findings will be integrated through thematic synthesis based on Braun and Clarke’s six-phase framework. Quantitative results will be transformed into narrative form and synthesized with qualitative data. Given the anticipated heterogeneity, a meta-analysis will not be conducted. Conclusion The findings are expected to provide insights into clinical nurses’ research capacity and its influencing factors to inform targeted strategies to support research engagement and integration into clinical practice.